Clostridium novyi-NT can cause regression of orthotopically implanted glioblastomas in rats - Staedtke, Verena (Oncotarget, 2015)
Glioblastoma (GBM) is a highly aggressive primary brain tumor that is especially difficult to treat. The tumor's ability to withstand hypoxia leads to enhanced cancer cell survival and therapy resistance, but also yields a microenvironment that is in many aspects unique within the human body, thus offering potential therapeutic opportunities. The spore-forming anaerobic bacterium Clostridium novyi-NT(C. novyi-NT) has the ability to propagate in tumor-generated hypoxia, leading to oncolysis. Here, we show that intravenously injected spores of C. novyi-NT led to dramatic tumor destructions and significant survival increases in implanted, intracranial syngeneic F98 and human xenograft 060919 rat GBM models. C. novyi-NT germination was specific and confined to the neoplasm, with sparing of the normal brain parenchyma. All animals tolerated the bacteriolytic treatment, but edema and increased intracranial pressure could quickly be lethal if not monitored and medically managed with hydration and antibiotics. These results provide pre-clinical data supporting the development of this therapeutic approach for the treatment of patients with GBM.